Fostering Ethical Engagement Across Religious Difference in the Context of Rhetorical Education - Michael-John DePalma (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
At a moment in which religious diversity is ever-increasing in the United States and more than three-quarters of the world’s population identifies with a religious tradition, it is important for writing teachers to consider how to best cultivate writers who are equipped to build identifications across religious difference. This essay traces my efforts to engage this exigence in my advanced undergraduate writing course at Baylor University entitled Religious Rhetorics and Spiritual Writing (RRSW). In what follows, I outline my pedagogical goals, course design, and approach to teaching RRSW. I then share the results of a qualitative pilot study that used teacher-research methodology to develop an understanding of what students learned about engaging across religious difference in RRSW. Results of this study show that students learned the value of approaching rhetorical engagement across religious difference with dispositions of hospitality, curiosity, and humility. Specifically, they came to see 1) the importance of using language that is grounded in writers’ personal histories and accessible to (religiously) diverse audiences; 2) the value of approaching religious and spiritual writing as a process of inquiry; and 3) the significance of holding capacious notions of religious and spiritual rhetorics. After discussing the implications of students’ learning in RRSW, I conclude the essay by articulating ways that more intentional engagement with scholarship in interfaith studies can assist teachers of writing in our efforts to enrich writers’ capacities to engage with religious difference in productive ways. “Our sacred traditions should help us live more thoughtfully, generously, and hopefully with the tensions of our age. But to grasp that, we must look anew at the very nature of faith, and at what it might really mean to take religion seriously in human life and in the world.” —Krista Tippett, Speaking of Faith: Why Religion Matters—and How to Talk about It “We must treat one another with empathy, attentiveness, and trust; we must take the time to invent and continually reinvent our ideas in the light of informed disagreement; we must care enough about our own views to try to persuade others of them, but not so much that we are unwilling to change them; we must listen with care to people who tell us we are wrong; we must behave with grace when other views prevail; we must argue with passion but without rancor, with commitment but without intransigence.” —Patricia Roberts-Miller, Deliberate Conflict: Argument, Political Theory, and Composition Classes
Keywords: Ethics; Religion; Rhetorical Education